Genitourinary involvement in Klippel–Trénaunay syndrome: pathophysiology, evaluation, and management - Lin, Weilong; Xie, Chong; Wang, Huaijie; Yang, Weijia; Wang, Peihua; Guo, Zhengtuan (Frontiers in Surgery, 2025)
Klippel–Trénaunay syndrome (KTS) typically involves a combination of capillary, lymphatic, and venous malformations of the lower extremities. Genitourinary involvement is frequently observed in patients with KTS. Bleeding and pelvic pain are the most common complications. This condition has been increasingly reported in recent years. However, most authors have only depicted extreme presentations or various combinations of clinical findings. The underlying pathophysiology of genitourinary involvement in KTS remains unclear. Genitourinary involvement in female patients with KTS has a more complicated pathophysiology than that in male patients with KTS. After understanding its pathophysiology, some patients can be successfully managed by using a staged plan. Therefore, recognizing the pathophysiology of genitourinary involvement is necessary for practitioners to evaluate and determine adequate management. Owing to the complexity and rarity of this condition, a prospective controlled study involving a large cohort of patients is impossible. Based on a literature review and our practice, we discuss the pathophysiology, evaluation, and treatment strategies for genitourinary involvement in KTS.